Investigating on-field decision making in Rugby Union - Sherwood, S. (2019)
Quick, accurate decision making in sport is essential for successful performance. In this five study thesis, psychological elements of decision making were investigated, guided by real world challenges encountered in a professional rugby organisation. Chapter 1 provided a background and review of relevant literature. Chapters 2 and 3 focused on pattern recall, an individual`s ability to recollect specific patterns from previous experiences. The results of Chapter 2 showed that professional players with more years of rugby experience were more accurate when recalling structured patterns. However, it was shown that pattern recall tasks did not predict on-field decision making performance and thus did not warrant inclusion in talent identification programs. Chapter 2 concluded that more appropriate stimuli (structured and semi-structured patterns) should be included in future studies to investigate the viability of pattern recall tasks for talent identification purposes. Chapter 3 found that a high tendency for decision reinvestment (a predisposition to consciously process decision-making) led to slower and less accurate performance on pattern recall tasks. In Chapter 4, the effect of reinvestment (movement specific and decision specific) and expertise on anticipation of deceptive and non-deceptive movements was investigated. The results showed experts to be significantly more accurate than novices at anticipating both deceptive and non-deceptive movements. It was also found that experts took significantly longer to respond than novices. Decision reinvestment did not play a role in anticipatory performance; however, increased movement reinvestment tendencies were associated with poorer anticipatory accuracy of deceptive movements. Both Chapter 5 and Chapter 6 investigated the decoy runners tactic, which is a novel form of deception in the literature to date, as it centres on players who are not in possession of the ball. The tactic involves multiple players in an attacking team running option lines off the ball carrier, making it possible that any of the players could receive the ball. Runners who do not receive the ball are decoys who aim to create confusion in defences. It was shown that decoy runners were significantly more effective when they displayed certain characteristics to attract defenders` attention (i.e., hands up as if receiving the ball and line change as if exploiting a gap in the defensive line). Chapter 6 followed up on a claim made in the discussion of Chapter 5, that the increased effectiveness of decoy runners (when displaying certain characteristics) was caused by momentary inattentional blindness of the player who received the ball. This study showed that the player who received the ball was more likely to be unnoticed when attention was diverted by a secondary task - fitting the description of inattentional blindness (an individual failing to register an unexpected object clearly within their field of vision when their attention is diverted to another object or task (Mack & Rock, 1998)). The findings are summarised and discussed in the context of relevant research in the decision making field. Practical applications for coaches are provided and future directions for research are considered.